Influence of filling sequence of concrete faced rockfill dam on deformation of squeezed sidewall and dam - Hongru, Li; Min, Yang; Jiaqi, Li (Frontiers in Earth Science, 2023)
During construction of concrete faced rockfill dam (CFRD), the extrusion-sidewall will be protruding or deficiency under normal，take the local cutting or filling after excavation of extrusion-sidewall before the concrete faces construction, thus will be influenced on stress and deformation of the concrete faces. According to the monitoring data of concrete-faced rockfill dams of some hydro-electric station in Hubei Province, using three-dimensional finite element analysis method, simulated CFRD filling original order process, compared the difference of monitoring and calculated data, reappeared the deformation of extrusion-sidewall and dam, verified the reasonability through the three-dimensional finite element analysis method. Compared the characteristic value of settlement and horizontal displacement that is numerical calculated and monitored of this dam to other high CFRD，the characteristics of the dam value is close to the range of values of the concrete face rockfill dam commonly. Studied deformation law of crushing-type side wall and dam under two optimization different filling sequence, found it is allowed, that first filling the upstream, then filling the downstream as far as possible, in order to reduce extrusion deformation of the upstream of the sidewall.